2012
DOI: 10.4312/ala.2.1.61-72
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Representation of Emotions in Japanese and Hungarian: Quantity and Abstractness

Abstract: In the present paper, two linguistic aspects of emotion expression are studied in the form they are performed in present day Japanese and Hungarian. After a brief summary on the recent emotional researches connected to Japanese culture and language, the concept of Linguistic Category Model is introduced. The quantitative study presented afterwards investigates emotion expression in terms of amount and abstraction. Translations were used for comparison and the results showed that 1) Japanese tend to use less ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Japanese cultural scripts that govern the order in which emotions are expressed and understood(Wierzbicka, 1996), emotional inference (Uchida et al, 2009), and the co-occurrence of positive and negative emotions in Japan (Miyamoto, Uchida, Ellsworth, 2010; Uchida and Kitayma, 2009) 3. Recent research in word recognition has reported an interaction between the emotional quality of a word (characterized as positive, negative, or neutral) and frequency of occurrence (more or less common usage).…”
mentioning
confidence: 99%
“…Japanese cultural scripts that govern the order in which emotions are expressed and understood(Wierzbicka, 1996), emotional inference (Uchida et al, 2009), and the co-occurrence of positive and negative emotions in Japan (Miyamoto, Uchida, Ellsworth, 2010; Uchida and Kitayma, 2009) 3. Recent research in word recognition has reported an interaction between the emotional quality of a word (characterized as positive, negative, or neutral) and frequency of occurrence (more or less common usage).…”
mentioning
confidence: 99%